Portfolio inertia and [epsilon]-contaminations - Takao Asano (Osaka University, Institute of Social and Economic Research (ISER), 2004)
This paper analyzes investors' portfolio selection problems in a two-period dynamic model of Knightian uncertainty. We account for the existence of portfolio inertia in this two-period framework. Furthermore, by incorporating investors' up-dating behavior, we analyze how new observation in the first period will affect investors' behavior. By this analysis, we show that new observation in the first period will expand portfolio inertia in the second period compared with the case in which new observation has not been gained in the first period if the degree of Knightian uncertainty is sufficiently large.
Keywords: 330; Portfolio-Management; Anlageverhalten; Theorie; Entscheidung bei Unsicherheit